Functional Verieties of a Dependent Sentence with the Conjunction “რაკი” - Pilashvili, Elene ("Intercultural Dialogues" Transactions, 2023)
Abstract Adjective is one of the organizing components of the sentence structure. Adjectives sharing the same sound composition carry various semantics, participate in different constructions and have a certain function. The conjunction რაკი is used in a hypotaxic construction containing circumstantial dependent clauses of time and cause. Circumstantial dependent clauses of time and cause principally differ from each other in their content, but sometimes it is difficult to accurately qualify the conditional dependent clauses because, apart from formal coincidences, they adapt to the conjunction and the grammatical forms of time and mood of verb-predicate, at the same time the categories of time and cause are closely related to each other. Based on the materials analysed below, we can coclude that the grammatical category of verb—predicate principally matters in identifying the sentences of hypotexic constraction containing the conjunction “რაკი’. Since the cause is to be sought in the past, it reflects the previous event and adjusts to the indicative mood; while the circumstantial dependent clause of time, which is linked with the main clause starting with the conjunction “რაკი”, shows the beginning of the action conveyed in the main clause, and the main clause shows what happened, is happening or will happen in the dependent clause after the indicated action. In case of disputed forms, in order to clarify the function of the the conjunction “რაკი” and distinguish hypotaxic constructions, method of replacing another conjunction and transferring the verb-predicate to the future tense are hily recomended, i.e. if the conjunction “because/as long as” is unable to completely replace the conjunction “რაკი” and the future tense form of the replaced verb-predicate is unnatural, in such case it belongs to the construction of the circumstantial dependent clause of time; in case it is easily replacable then the dependent clause is circumstantial of cause.